Impact of health facility delivery and antenatal care on neonatal mortality in Sub-Saharan Africa: a propensity score matching analysis - Meklit Melaku Bezie; Bezawit Melak Fente; Zufan Alamrie Asmare; Angwach Abrham Asnake; Hiwot Atlaye Asebe; Yohannes Mekuria Negussie; Beminate Lemma Seifu (BMC Pregnancy and Childbirth)
Abstract Background Even though global neonatal mortality has shown a remarkable reduction, it still constitutes 42% of the global under-five mortality. Nearly three-fourths of these deaths occurred in sub-Saharan Africa (SSA). Antenatal Care (ANC) and health facility delivery are the best-recommended strategies to prevent neonatal mortality. Previously published studies showed a significant association between ANC and health facility delivery with neonatal mortality. However, none of them examined the actual causal impact of health facility delivery and ANC on neonatal mortality in SSA using Propensity Score Matching (PSM) analysis. Therefore, our study examined the causal effect of ANC and health facility delivery on neonatal mortality in SSA using the Propensity Score Matched (PSM) analysis approach. This study adds new knowledge to the existing literature by evaluating the actual effect of health facility delivery and antenatal care on neonatal mortality by controlling confounding via matching. Which in turn enable decision makers in evaluating the effectiveness of these services in reducing neonatal mortality in SSA. Methods We used the Demographic and Health Survey (DHS) data of 28 sub-Saharan African countries. About 351,940 live births were considered for this study. STATA version 18 statistical software was used for data management and analysis. We employed the Propensity Score Matching (PSM) analysis to examine the causal effect of ANC and health facility delivery on neonatal mortality. The logit model was fitted to estimate the propensity score. In the final PSM model, the average treatment effect of ANC and health facility delivery on neonatal mortality were reported. The quality of matching was checked to ensure the robustness of the results. We did sensitivity analysis to test hidden bias using the Mantel-Haenzel (MH) test statistic. Results Neonatal mortality in SSA was 27.36 (95%: 26.83, 27.90) per 1000 live births. The Average Treatment Effect on the treated (ATT) in the PSM analysis demonstrated that ANC and health facility delivery decrease the risk of neonatal mortality by 1.04% and 0.22%, respectively. Similarly, the Average Treatment Effect on the Population (ATE) showed that ANC and health facility delivery reduce neonatal mortality by 1.04% and 0.22%, respectively. The quality of matching was good and the results were not sensitive to hidden bias. The treatment and control groups were well comparable for the baseline confounders after matching (p-value > 0.05). Conclusion Our study found that ANC and health facility delivery significantly contributed to the reduction of neonatal mortality after matching the treatment and control groups by observed variables. These findings highlighted that maternal and newborn health care programs and policies could enhance maternal health service utilization in SSA to reduce neonatal mortality.